2017
DOI: 10.1111/cid.12573
|View full text |Cite
|
Sign up to set email alerts
|

Micromotion analysis of different implant configuration, bone density, and crestal cortical bone thickness in immediately loaded mandibular full‐arch implant restorations: A nonlinear finite element study

Abstract: Background: Excessive micromotion may cause failure of osseointegration between the implant

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…We can assume that by removing the mechanically incompatible transition we extend the life of the implant by limiting the micro-motions occurring on the ramp change of stiffness at the interface between bone and bulk titanium. 62 As similar hardness trends (Fig. 11) were observed by Crawford et al 2007 and Xu et al 2015.…”
Section: Discussionsupporting
confidence: 85%
“…We can assume that by removing the mechanically incompatible transition we extend the life of the implant by limiting the micro-motions occurring on the ramp change of stiffness at the interface between bone and bulk titanium. 62 As similar hardness trends (Fig. 11) were observed by Crawford et al 2007 and Xu et al 2015.…”
Section: Discussionsupporting
confidence: 85%
“…This is especially true for cancellous bone, where the Young's modulus can vary from 0.1 to 4.5 GPa depending on bone density and trabecular orientation [28]. A comparison of the obtained results to the Young's modulus of the cancellous bone (1.37 GPa) [27] has shown that the closest value was obtained for A-type samples (1.26 GPa). It is possible that the use of A-type geometry structures as a fill of the modeled implant could reduce the phenomenon of stress shielding.…”
Section: Discussionmentioning
confidence: 81%
“…11) and registration of pores with diameters exceeding 147 µm. Pores with the largest equivalent diameters [27] (larger than 7 mm) and the most extensive surface areas (greater than 40 mm 2 ) were registered for C-type sample. Pores with the smallest equivalent diameters (less than 3.5 mm) and the smallest surfaces (less than 20 mm 2 ) were recorded for D-and E-type samples (Fig.…”
Section: Geometric Analysis Using Ctmentioning
confidence: 96%
“…The stability and pull-out strength of OMIs depend upon the thickness and density of the existing cortical bone (Ardani et al, 2019;Elibol et al, 2020). Cancellous bone was also assessed in the present study adding to the literature available on the role of cancellous bone in the primary stability of OMIs (Ohiomoba et al, 2017;Sugiura et al, 2018). The point of difference in this study was using computed tomography (CT) to evaluate bone density at different interradicular regions as well as in the infrazygomatic crest (IZC) region considering the higher diagnostic capability of CT images (Ohiomoba et al, 2017).…”
Section: Introductionmentioning
confidence: 99%